2008
DOI: 10.1007/s10653-008-9168-7
|View full text |Cite
|
Sign up to set email alerts
|

Environmental health impacts of East African Rift volcanism

Abstract: The East African Rift Valley (EARV) is a structure of a major order in the Earth's crust. Accompanying volcanic activity has influenced greatly the nature of the soils and the geochemistry of ground and surface waters, an influence that is reflected in water and food quality. Direct volcanic impacts result from the up-welling of volatile, potentially harmful elements (PHE), such as F, As, and Hg, that dissolve directly into groundwaters. Intense tropical weathering results in clear redistribution of all but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Soils are potentially attractive for animals, with high Ca, Mg, Ca and K contents, but these advantages are offset by other factors. The vegetation growing on these soils often has low Ca and Mg levels, as noted earlier, and geophagia (the practice of eating soil-like substrates) is common today in this part of the Kenya Rift for both humans and animals (Davies, 2008). 'Salt licks' at places where lake beds are (Table S1, Figure S2) contains complete data.…”
Section: Interpretation Of Animal Distributionsmentioning
confidence: 98%
“…Soils are potentially attractive for animals, with high Ca, Mg, Ca and K contents, but these advantages are offset by other factors. The vegetation growing on these soils often has low Ca and Mg levels, as noted earlier, and geophagia (the practice of eating soil-like substrates) is common today in this part of the Kenya Rift for both humans and animals (Davies, 2008). 'Salt licks' at places where lake beds are (Table S1, Figure S2) contains complete data.…”
Section: Interpretation Of Animal Distributionsmentioning
confidence: 98%
“…Fluoride is generally occurring in high concentrations in waters along most of the East African Rift System (e.g. Kilham and Hecky, 1973;Nanyaro et al, 1984;Gaciri and Davies, 1993;Apambire et al, 1997;Nielsen and Dahi, 2002;Reimann et al, 2003;Davies, 2008) and many studies have shown a high prevalence of both dental and skeletal fluorosis in the region (e.g. Shorter et al, 2010;Rango et al, 2012) .…”
Section: Health Hazards Caused By Excess Fluoridementioning
confidence: 99%
“…Accordingly, most of the cases of environmental health conditions involving dietary fluorine imbalance are reported for populations living within the African rift zones and associated volcanic centres (Davies, 2008). Accordingly, most of the cases of environmental health conditions involving dietary fluorine imbalance are reported for populations living within the African rift zones and associated volcanic centres (Davies, 2008).…”
Section: Fluorinementioning
confidence: 99%
“…Davies, 2008), and these may cause more toxicity problems in humans than dust components from other sources. Davies, 2008), and these may cause more toxicity problems in humans than dust components from other sources.…”
Section: Geogenic Dustmentioning
confidence: 99%